1990
DOI: 10.1021/ie00106a019
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic effects using semicontinuous vis-a-vis discrete descriptions in phase equilibrium computations

Abstract: The use of continuous vis4-vis discrete descriptions for the C7+ portion of a live oil is examined for a calculation especially sensitive to the nature of the C7+ description, specifically, liquid dropout near an upper dew point of a live oil + gas mixture. Conservation-of-mass failure in the semicontinuous flash problem, a recognized formal shortcoming of continuous thermodynamics, is shown to lead to a previously unexplained bias that occurs in saturation calculation results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…We deemed this necessary from comparisons of calculated roots and weighting factors with literature tabulations for the case C --»(Abramowitz and Stegun, 1972). All computations were performed using the same Redlich-Kwong equation of state description as employed in our earlier paper (Luks et al, 1990). It should be emphasized that the choice of equation of state is not crucial here, only that the same equation of state description be used in comparative computations.…”
Section: Example Calculationmentioning
confidence: 99%
“…We deemed this necessary from comparisons of calculated roots and weighting factors with literature tabulations for the case C --»(Abramowitz and Stegun, 1972). All computations were performed using the same Redlich-Kwong equation of state description as employed in our earlier paper (Luks et al, 1990). It should be emphasized that the choice of equation of state is not crucial here, only that the same equation of state description be used in comparative computations.…”
Section: Example Calculationmentioning
confidence: 99%
“…With respect to such continuous systems, it has been shown that quadrature can be a very effective way of specifying the pseudocomponents of the C 7+ portion of an oil, provided one can accurately represent the distribution of the many species as a continuous function of some parameter(s), say, the carbon number. Additionally, quadrature discretization can be shown to avoid certain conservation of mass inconsistencies that are inherent in the continuous formalism of phase equilibrium computations, including saturation computations …”
Section: Introductionmentioning
confidence: 99%
“…While there have been many papers addressing phase equilibrium calculations for single-stage processes (bubble point, dew point, various flash and cloud point calculations) , there are few detailed demonstrations of continuousmixture thermodynamics for multistage processes. The mathematical problems of maintaining mass balances and the limitations of assuming closed form distribution functions are well-known (Luks et al, 1990;Sandler and Libby, 1991). These mathematical difficulties may be overcome, but at the expense of a number of physical/ chemical assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the method of moments was invoked for flow distribution functions, which were of a fixed (Gaussian) form. The shortcomings of the method of moments have been discussed (Luks et al, 1990; Sandler and Libby, 1991).…”
Section: Introductionmentioning
confidence: 99%